ANALYSIS OF THE QUALITY OF SUROBOYO BUS PERFORMANCE ON PUBLIC TRANSPORTATION SERVICE USERS - Deni Setyawan; Rensa Heka Satriani Sumadita; Sofi Putri Febrianti (Irpia : Jurnal Ilmiah Riset dan Pengembangan, 2025)
This article discusses the performance of Suroboyo bus services. Suroboyo is a transportation based on Bus Rapid Transit.This public transportation is a transportation that has been issued by the Surabaya City Government for almost 6 years with various routes in the middle of the city, the formation of the Surabaya Bus is to reduce congestion and make it easier for Surabaya residents to access transportation. Therefore, the study was conducted to determine customer assessment of the quality of Suroboyo Bus service.In this study, independent variables use the SERVQUAL (Service Quality) method which has five important dimensions, namely (1) Tangible, (2) Reliability, (3) Empathy, (4) Assurance, and (5) Responsiveness. This research uses a qualitative method with secondary data sources in the form of statistics, reports, articles, documents and related sources. This research collected data through two stages, namely observation and documentation. Based on the results of the research, the service performance provided has not met the expectations of customers/passengers. However, customers feel that the service provided is quite satisfactory. In addition, there are several facilities that must be prioritized for improvement, namely improving passenger facilities at bus stops, such as providing comfortable seats, adequate lighting and so on, as well as the responsiveness of officers to improve the level of customer satisfaction and service quality